Targeting Mitochondrial and Brain Injury Markers in Acquired Brain Injuries: A Randomized, Double-Blind, Placebo-Controlled Study with Melatonin - Bahareh Hakiminia; Babak Alikiaie; Fariborz Khorvash; Sarah Mousavi (Tabriz University of Medical Sciences, 2022)
Purpose: Oxidative stress-induced mitochondrial damage is the main event in acquired brain injuries (ABI). This study aimed to evaluate the effects of melatonin, a mitochondria-targeted antioxidant, on mitochondrial and brain injury markers, and the clinical outcomes of patients with ABI. Methods: In this randomized controlled trial, intensive care unit (ICU) or neurology patients with ABI (n=60) received melatonin (21 mg/day) or placebo tablets, within the first 72 hours of injury onset for five days. As a primary endpoint, serum levels of malondialdehyde (MDA), S100B and C-reactive protein (CRP) were compared at baseline, and after five days' intervention. Secondary endpoints included assessment of Glasgow Coma Scale and Sequential Organ Failure Assessment (at the end of day 5), Rancho Los Amigos Revised Scale and modified Rankin Scale (at the end of month 3), the duration of mechanical ventilation, the lengths of ICU and hospital stays, and in-hospital and three-month mortality. Results: There were no significant effects of melatonin on the primary and secondary outcomes. However, the subgroup analysis showed a significant reduction in S100B in patients with non-traumatic brain injuries, receiving melatonin versus placebo (p: 0.016). Conclusion: This study showed that melatonin supplementation in the early phase of brain injury had no significant effects on the injury markers and clinical outcomes of patients with ABI. However, it reduced the level of S100B in the non-traumatic subgroup. Further larger-scale studies are needed to determine the effects of melatonin on the ABI and its subgroups.